The Relationship between Motivation for, and Interest in, Learning Physics among Lower Secondary School Students in Uganda. Issue 3 (1st September 2020) - Kwarikunda, Diana; Schiefele, Ulrich; Ssenyonga, Joseph; Muwonge, Charles Magoba
Abstract : Motivation and interest affect students' learning especially in Physics, a subject learners perceive as abstract. The present study was guided by three objectives: (a) to adapt and validate the Science Motivation Questionnaire (SMQ-II) for the Ugandan context; (b) to examine whether there are significant differences in motivation for learning Physics with respect to students' gender; and (c) to establish the extent to which students' interest predicts their motivation to learn Physics. The sample comprised 374 randomly selected students from five schools in central Uganda who responded to anonymous questionnaires that included scales from the SMQ-II and the Individual Interest Questionnaire. Data were analysed using confirmatory factor analyses, t -tests and structural equation modelling in SPSS-25 and Mplus-8. The five-factor model solution of the SMQ-II fitted adequately with the present data, with deletion of one item. The modified SMQ-II exhibited invariant factor loadings and intercepts (i.e. strong measurement invariance) when administered to boys and girls. Furthermore, motivation for learning Physics did not vary with gender. Students' interest was related to motivation for learning Physics. Lastly, although students' interest significantly predicted all motivational constructs, we noted considerable predictive strength of interest on students' self-efficacy and self-determination in learning Physics. Implications of these findings for the teaching and learning of Physics at lower secondary school are discussed in the paper.